Utility of check list for neck pain history: student and teacher perceptions - Desai, Niyati A.; Khatri, Subhash (International Journal Of Community Medicine And Public Health, 2017)
Background: Teaching and learning of clinical skills for medical and paramedical students believed to be a crucial phase. The primary purpose of this study was to identify the teaching behaviours perceived to be the most effective and those to be the most hindering with the investigator developed check list for neck pain history. Methods:Forty seven students and eight clinical teachers participated in the present study. Clinical teaching session on neck pain history was carried out by a clinical teacher and performance recorded with the investigator developed check list. Then one student was asked to take a focused history from a neck pain patient followed by scoring. After this, they were provided a copy of check list to read and then they were requested to re-obtain the history. Score difference was noted. Student and teacher perceptions about the utility and limitations of using check list in teaching and learning was taken. Results: Behaviours perceived as most helpful and hindering by both students and clinical teachers are ranked and listed as per their mean value. Conclusions:Use of the check list for neck pain history can facilitate a favourable learning and teaching environment.